COLLABORATION IN THE MANAGEMENT OF THE PALUTUNGAN CLIMBING ROUTE IN CIREMAI MOUNTAIN NATIONAL PARK - Juanto, Agus Anto; Putri, Aprilia Sabila; Hidayat, Moh. Taufik; Nursahidin (Veredas do Direito, 2026)
The strengthening of nature tourism is encouraged by national policies as stipulated in Government Regulation No. 36 of 2010 concerning Nature Tourism in Wildlife Reserves, National Parks, Grand Forest Parks, and Nature Parks. The Palutungan Climbing Trail is one of the tourist destinations in Gunung Ciremai National Park. The management of the Palutungan Climbing Trail is carried out by the Gunung Ciremai National Park Office (BTNGC) in collaboration with the surrounding community under the auspices of the Rimba Cipta Lestari Cooperative (Ricis). This study aims to determine how management and factors as well as efforts are carried out through the collaborative relationship between BTNGC and Ricis using the collaboration process theory proposed by Ansell and Gash (2008). Using a qualitative case study approach, the study involved interviews with informants using purposive sampling techniques, field observations, and document studies. The results of this study explain that collaboration in the management of the Palutungan Climbing Trail began with the initial collaboration between BTNGC and Ricis. The institutional design for the management of the Palutungan climbing trail can be said to have fulfilled the basic elements of collaboration. The leadership of BTNGC was able to facilitate cross-sector dialogue through the Ciremai Tourism Forum and informal approaches that were able to bridge the interests between sectors. The decision-making process prioritizes participation and deliberation, in which each key actor presents their ideas and suggestions at cross-sector forums to design and implement the programs to be developed. The resulting collaborative process has improved the management of the Palutungan hiking trail, developed hiking tourism, and provided economic benefits to the local community. The inhibiting factors are limited communication and the quality of human resources, which have resulted in low participation in collaborative activities. The assistance, monitoring, and evaluation activities of BTNGC are steps to improve communication and human resource quality for better collaboration between BTNGC and Ricis in managing the Palutungan hiking trail.